1993
DOI: 10.1002/gps.930080609
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol abuse in an inner city elderly population: The gospel oak survey

Abstract: SUMMARYOne hundred and seventy-nine men and 335 women over the age of 65 years, ascertained in a community survey, completed the CAGE questionnaire to detect possible alcohol abuse. Only three subjects were CAGE positive and thus at risk for alcohol abuse. It is concluded that current alcohol abuse does not underlie neuropsychiatric conditions in the elderly and fears of significant rates of abuse in this population are probably unfounded. Further research is necessary.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

1994
1994
2014
2014

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 17 publications
(24 reference statements)
0
3
0
1
Order By: Relevance
“…A sample from a general practice of those over 60 found a 23% dependence rate in men and 11% in women (Bridgewater et al, 1987). However, a study of 514 people over 65 years of age found only three people who scored over two positive replies in the CAGE questionnaire (Livingstone and King, 1993). Our ®ndings appear to indicate that alcohol abuse in the elderly is either poorly detected by health professionals (McInnes and Powell, 1994) or that the elderly with alcohol problems are reluctant to consult their general practitioner for help.…”
Section: Consultation Rates For Psychiatric Diagnosesmentioning
confidence: 52%
“…A sample from a general practice of those over 60 found a 23% dependence rate in men and 11% in women (Bridgewater et al, 1987). However, a study of 514 people over 65 years of age found only three people who scored over two positive replies in the CAGE questionnaire (Livingstone and King, 1993). Our ®ndings appear to indicate that alcohol abuse in the elderly is either poorly detected by health professionals (McInnes and Powell, 1994) or that the elderly with alcohol problems are reluctant to consult their general practitioner for help.…”
Section: Consultation Rates For Psychiatric Diagnosesmentioning
confidence: 52%
“…The poor sensitivity of the CAGE casts doubt on those studies in the UK which report the prevalence of alcohol problems using it to de®ne alcohol misuse in older people (Bridgewater et al, 1987;Livingston and King, 1993).…”
Section: Discussionmentioning
confidence: 98%
“…6 A recent community survey in London revealed similar results. 7 In contrast, Bridgewater et al 8 found that 23% of men and 11% of women aged 60+ in a sample 101 general practice patients in Newcastle were classified as having alcohol problems.…”
Section: Incidence and Prevalencementioning
confidence: 92%